2020
DOI: 10.1063/1.5129647
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of copper and copper oxide nanomaterials by electrical discharges in water with various electrical conductivities

Abstract: Nano-second temporal particle behavior in high-power impulse magnetron sputtering discharge in a cylindrical cathode

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…The SAED pattern and resulting radially integrated spectrum of these agglomerates presented interplanar distances corresponding to Cu 2 O crystals as well as Cu ( d (111) = 2.09 Å and d (200) = 1.81 Å) ( Figure 9 b). This indicates that the nanoparticles were not oxidized (if oxidized, a shift in d towards smaller values is usually observed [ 22 , 25 ]). Knowing that Cu can be easily oxidized in water or upon exposure to ambient air, one may assume that the synthesized Cu nanoparticles were embedded in a matrix of Cu 2 O nanowires, which may protect Cu particles from oxidation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The SAED pattern and resulting radially integrated spectrum of these agglomerates presented interplanar distances corresponding to Cu 2 O crystals as well as Cu ( d (111) = 2.09 Å and d (200) = 1.81 Å) ( Figure 9 b). This indicates that the nanoparticles were not oxidized (if oxidized, a shift in d towards smaller values is usually observed [ 22 , 25 ]). Knowing that Cu can be easily oxidized in water or upon exposure to ambient air, one may assume that the synthesized Cu nanoparticles were embedded in a matrix of Cu 2 O nanowires, which may protect Cu particles from oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…Their SAED patterns show concentric circles with radii corresponding to specific interplanar distances, d hkl , which allow the determination of their crystalline structure. Herein, we used a previously developed method [ 22 , 24 ] to transform the SAED pattern into a radially integrated spectrum where each peak corresponds to the sum of the different diffraction spot at fixed d hkl values (i.e., fixed radius from the non-diffracted beam, in the reciprocal space). The peaks identified in Figure 8 b thus suggest that the nanowires are composed of Cu 2 O crystals ( d (110) = 3.012 Å, d (111) = 2.464 Å, d (200) = 2.136 Å, d (220) = 1.510 Å, d (311) = 1.287 Å, and d (222) = 1.232 Å).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…or the liquid solution (e.g., heptane 6 and other liquid hydrocarbons (HCs) 7 , liquid nitrogen 5 ). Using copper electrodes in water, Glad et al 8 synthesized various Cu-based nanostructures whose oxygen content can be controlled by adjusting (adding HCl) the electrical conductivity of water. Other studies have demonstrated that discharges between metal electrodes in HC liquids can produce nanocomposite materials such as metal nanoparticles embedded in an amorphous matrix 9 .…”
Section: Introductionmentioning
confidence: 99%